1986
DOI: 10.1071/mf9860467
|View full text |Cite
|
Sign up to set email alerts
|

Effects of food quality and quantity on the survival, development, and egg production of Gladioferens pectinatus (Brady) (Copepoda : Calanoida)

Abstract: Effects of food quality and quantity on certain fitness traits of G. pectrnatus were examined to develop methods of culture. Five generations were successfully reared on excess Isochrysis galbana, despite intense inbreeding. The effect of food quantity was tested using outcrossed offspring fed I. Galbana at four concentrations. Generation time (from hatching to egg) decreased from 43.2 days at 1 × 104 cells ml-1 (lowest concentration) to 19.6 days at 5 × 105 cells ml-1 (highest concentration). An increase occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Increased nauplii densities may have resulted in increased survival and maturation into copepodite stages, leading to the higher copepodite and adult densities observed. Arnott et al () has shown G. pectinatus lays more eggs and has greater maturation success in the presence of more available food resources.…”
Section: Discussionmentioning
confidence: 99%
“…Increased nauplii densities may have resulted in increased survival and maturation into copepodite stages, leading to the higher copepodite and adult densities observed. Arnott et al () has shown G. pectinatus lays more eggs and has greater maturation success in the presence of more available food resources.…”
Section: Discussionmentioning
confidence: 99%
“…Their importance is qualitative since certain phytoplanktonic fatty acids are essential for higher trophic levels (Siron et al 1989). As has been demonstrated in many studies, a dietary deficiency of PUFAs in phytoplankton can limit the growth of several herbivores (Watanabe et al 1983, Arnott et al 1986, Huntley et al 1987, Volkman et al 1989). In the marine environment such an impact of UV-B radiation on the biochemical status of phytoplankton could thus have serious consequences on the food chain (Claustre et al 1989).…”
Section: Relationship Between Fatty Acids and Pigmentsmentioning
confidence: 96%
“…UV-B radiation also has a negative influence on several other cellular enzymes and biochemical processes within phytoplankton (Newton et al 1979, Dohler 1984, 1985, 1989a, b, 1990, 1992, Hader et al 1986, Dohler et al 1987, 1991, leading us to question whether an enhancement in natural levels of UV-B radiation could have a significant impact on the formation of biochemical compounds within phytoplankton cells. This question assumes considerable significance, as the biochemical composition of phytoplankton determines its nutritive value for higher trophic organisms (Watanabe et al 1983) and is critical during growth and development of herbivores (Arnott et al 1986, Huntley et al 1987, Claustre et al 1989. Despite this, there have been only a few studies which have examined the effect of UV-B radiation on the biochemical status of phytoplankton cells (Dohler 1984(Dohler , 198913, 1992 and references cited therein); this effect therefore remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Asterisks: * -significantly different, P = 0.05, F < j(0.95); ** -very significantly different, P = 0.01, F < (0.95); ns-nonsignificantly different. remating, and temperature (Watras and Haney 1980;Arnott et al 1986;Fransz et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Egg production and development rates in marine and freshwater copepods have been shown to depend on several factors, including food concentration and algal composition of the diet (Kiorboe et al 1985;Arnott et al 1986). In addition, egg production rates have been shown to be positively correlated with temperature (Sekiguchi et al 1980), female body size (Durbin et al 1992), reproductive condition (Ianora et al 1989), and remating (Parrish and Wilson 1978).…”
mentioning
confidence: 99%